Analisis Heatmap Korelasi dan Scatterplot untuk Mengidentifikasi Faktor-Faktor yang Mempengaruhi Pelabelan AC efisiensi Energi - Leni, Desmarita; ., Muchlisinalahuddin; ., Maimuzar; ., Haris; ., Hendra (Rekayasa Material, Manufaktur dan Energi, 2023)
This research aims to evaluate the factors that affect AC energy efficiency using statistical analysis methods. The data used is energy-efficient AC labeling data obtained from the Directorate General of New, Renewable, and Energy Conservation Energy (EBETKE) database. Violin plots are used to see the distribution of the data, a correlation heatmap is used to display the level of correlation between variables, and scatterplots and R-squared values are used to visualize linear relationships and measure the strength of the relationship. The results of the study show that efficiency has a very strong positive correlation with rating, with a correlation coefficient of 0.75, while it has a weak negative correlation with other variables. The R-squared value obtained for the linear relationship between efficiency and rating is 0.56, which indicates that 56% of the variation in efficiency can be explained by the variation in rating. This result shows that rating is a very influential factor on AC energy efficiency.